Inhibition of PI3K/mTOR Overcomes Nilotinib Resistance in BCR-ABL1 Positive Leukemia Cells through Translational Down-Regulation of MDM2 - Ding, Jie; Romani, Julia; Zaborski, Margarete; MacLeod, Roderick A. F.; Nagel, Stefan; Drexler, Hans G.; Quentmeier, Hilmar (PLOS ONE, 2013)
Chronic myeloid leukemia (CML) is a cytogenetic disorder resulting from formation of the Philadelphia chromosome (Ph), that is, the t(9;22) chromosomal translocation and the formation of the BCR-ABL1 fusion protein. Tyrosine kinase inhibitors (TKI), such as imatinib and nilotinib, have emerged as leading compounds with which to treat CML. t(9;22) is not restricted to CML, 20-30% of acute lymphoblastic leukemia (ALL) cases also carry the Ph. However, TKIs are not as effective in the treatment of Ph+ ALL as in CML. In this study, the Ph+ cell lines JURL-MK2 and SUP-B15 were used to investigate TKI resistance mechanisms and the sensitization of Ph+ tumor cells to TKI treatment. The annexin V/PI (propidium iodide) assay revealed that nilotinib induced apoptosis in JURL-MK2 cells, but not in SUP-B15 cells. Since there was no mutation in the tyrosine kinase domain of BCR-ABL1 in cell line SUP-B15, the cells were not generally unresponsive to TKI, as evidenced by dephosphorylation of the BCR-ABL1 downstream targets, Crk-like protein (CrkL) and Grb-associated binder-2 (GAB2). Resistance to apoptosis after nilotinib treatment was accompanied by the constitutive and nilotinib unresponsive activation of the phosphoinositide 3-kinase (PI3K) pathway. Treatment of SUP-B15 cells with the dual PI3K/mammalian target of rapamycin (mTOR) inhibitor BEZ235 alone induced apoptosis in a low percentage of cells, while combining nilotinib and BEZ235 led to a synergistic effect. The main role of PI3K/mTOR inhibitor BEZ235 and the reason for apoptosis in the nilotinib-resistant cells was the block of the translational machinery, leading to the rapid downregulation of the anti-apoptotic protein MDM2 (human homolog of the murine double minute-2). These findings highlight MDM2 as a potential therapeutic target to increase TKI-mediated apoptosis and imply that the combination of PI3K/mTOR inhibitor and TKI might form a novel strategy to combat TKI-resistant BCR-ABL1 positive leukemia.